COMPARISON OF TWO DIFFERENT PLATE TYPES IN THE MINIMALLY INVASIVE PERCUTANEOUS PLATE OSTEOSYNTHESIS OF DISTAL TIBIA FRACTURES - Nastov, Nebojsha; Bekteshi, Labinot; Todorov, Risto; Aleksova, Pavlina; Jovanovska, Elizabeta Stojovska (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Distal tibia fractures present a unique challenge for the surgeon due to the subcutaneous position of the tibia with a thin soft tissue envelope. The development of the technique for minimally invasive percutaneous plate osteosynthesis (MIPPO) is a well-accepted step towards this direction. In our study we explore the benefits and shortcomings of two different plate types used with this technique: the 3.5 mm anatomically pre-shaped titanium plate, and the 4.5 mm LC-DCP. The study was a prospective â€“ retrospective clinical intervention case control study of 100 patients with closed, unstable, extraarticular and partially articular fractures of the distal tibia and fibula, classified as AO type 43A1, 43A2 and 43Ð3. Patients were divided in two groups of 50 patients. Group A were patients prospectively treated with a 3.5 mm pre-shaped plate, and Group B were patients with retrospectively collected data treated with a 4.5 mm LC-DCP. Patietns age was 38.15 years with 68 male and 32 female patients. Operation duration in Group A was 57.14 Â± 8.30 and 66.67 Â± 5.55, in Group B which was statistically significant. Partial and full weight bearing, as well as time to union in both groups was achieved within a similar timeframe. Functional according to Johner and Wruh's criteria and showed that most patients in both groups (61) had excellent results (Group A: 32, Group B: 29) and 21 had good results (Group A: 10, Group B:11). Rate of complications were comparable between the two groups, in regard to superficial infection, deep infection and ankle stiffness. Only complication parameter which showed a significant difference between the two groups was rate of implant irritation, which was higher in the 4.5 mm LC-DCP group. Both 3.5 mm and 4.5 mm plates are reliable when used with a MIPPO technique. This method is minimally invasive, preserves the periosteal blood supply and ensures optimal conditions for biological repair of distal tibia fractures, regardless of the type of plate used. Keywords:  Distal tibia fractures, MIPPO, Distal Tibia LC-LCP, LC-DCP, AO-classification.